A Case Study: Understanding and Responding to Homelessness Crisis in Chilliwack - Stevens, Heather; Dhungel, Rita (Journal of Advanced Academic Research, 2024)
This paper presents an in-depth discussion on the breakdown of government programs over the last few decades that have eroded the low-to-middle income housing stock and ballooned housing unaffordability in BC with a focus on Chilliwack. The goals of this paper are twofold, and they include: (1) unpack the causes of homelessness and its implications; (2) examine the current responses to the homelessness crisis. Most of the data collection done to support this analysis is drawn from current news stories and government websites so that the most up-to-date and impactful happenings are incorporated. This article examines the root causes of homelessness followed by the highlights of existing solution efforts and gaps in programs and policies using a case example of Chilliwack, British Columbia, Canada. This paper briefly discusses the recommendations and next step to address the homelessness crisis in BC with a focus on Chilliwack.